Regeneration Limitations of Hippophae rhamnoides Population After Successfully Encroached on the Qinghai‐Tibetan Plateau - Baoli Fan; Pengfei Gao; Tingting Tian; Jinhua Jiang; Nana Ding; Yongkuan Wan; Miaojun Ma; Kun Sun (Ecology and Evolution)
ABSTRACT Shrub encroachment can alter the structure and function of grassland ecosystems, leading to their degradation. Therefore, population regeneration dynamics after shrub encroachment on the influence of grassland should not be ignored. H. rhamnoides, as a pioneer species, has significantly encroached with large areas on the Qinghai‐Tibetan Plateau (QTP) due to climate change and over‐grazing. However, few studies have focused on the dynamics of population regeneration following successful encroachment. Therefore, we studied H. rhamnoides natural population in the alpine grasslands, investigating population regeneration pattern, seed, bud production and storage, and limitation imposed by microhabitats (soil, light and feeding). Our aim was to explore population regeneration strategies and identify key limiting factors for population regeneration after successful encroachment. Our findings revealed several key points: (i) H. rhamnoides entered the alpine grassland by relying on seeds, it would seize resources by low‐cost clonal reproduction, then increase sexual reproduction to improve genetic diversity. (ii) The production and storage of seeds and buds was sufficient, seed vigor was high, seed emergence rate was higher due to mechanical restriction of hard seed coat was weakened by the water transport channels in the palisade layer, and formation of seedlings was less restricted. (iii) H. rhamnoides population regeneration was mainly limited by microhabitats light and feeding. However, light and feeding significantly affected seedlings photosynthesis and carbon storage, their interaction significantly reduced the seedlings survival, and further restricted population regeneration. The results can provide theoretical basis for the restoration and management of alpine grassland degradation caused by shrub encroachment.